2023
DOI: 10.1002/ejsp.2966
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal test of secondary transfer effects of negative intergroup contact and mediating processes

Abstract: Positive intergroup contact has not only been shown to be positively associated with favourable attitudes towards members of the contacted group but also with attitudes towards members of secondary outgroups (secondary transfer effect, STE). Only a few studies have addressed a potential STE of negative intergroup contact (i.e., a generalization of negative contact experiences to secondary outgroups). Furthermore, longitudinal studies on STEs and on underlying mediation processes are lacking. In the present res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…First, many intergroup interactions in real-life situations will be shaped by expectations and previous experiences. Even if direct intergroup contact might be scarce in some settings, other forms of intergroup experiences, such as extended and vicarious intergroup contact (Vezzali et al, 2014), contact with for example similar groups (Kauff et al, 2023), and media portrays of outgroups are likely to affect any intergroup interactions we would be able to implement in such a video game setting, as previous research demonstrated that previous experiences with the respective group will affect subsequent intergroup contact (e.g., Paolini et al, 2014;Schäfer et al, 2022). One important focus for future research should therefore be to examine the interplay of real-life experiences and experiences in virtual settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many intergroup interactions in real-life situations will be shaped by expectations and previous experiences. Even if direct intergroup contact might be scarce in some settings, other forms of intergroup experiences, such as extended and vicarious intergroup contact (Vezzali et al, 2014), contact with for example similar groups (Kauff et al, 2023), and media portrays of outgroups are likely to affect any intergroup interactions we would be able to implement in such a video game setting, as previous research demonstrated that previous experiences with the respective group will affect subsequent intergroup contact (e.g., Paolini et al, 2014;Schäfer et al, 2022). One important focus for future research should therefore be to examine the interplay of real-life experiences and experiences in virtual settings.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true, as intergroup contact effects might not only generalize to the specific outgroup, but also have secondary transfer effects (e.g., Lolliot et al, 2013), whereby outgroup attitudes generalize toward groups not involved in the interaction itself. Even though to date, evidence regarding a secondary transfer effect of negative contact is still scarce (e.g., Kauff et al, 2023), this possibility should not be neglected. Yet, this also bears opportunities for positive contact induced in such a paradigm to impact intergroup relations up and above the contact directly induced.…”
Section: Discussionmentioning
confidence: 99%